Interactive GIS Based Flood Risk Assessment for Illinois: Enhancing Preparedness, Planning, and Public Awareness - , Paul Osazuwa; , Ugochukwu Udonna Okonkwo; , Okpowe Omena; , James Mensah; , Olaoluwa Omidiji; , Ezekiel Tosin Babatunde; , Philip Ugbede Ojo Onuche; , Abdullahi Adams Opeyemi (Archives of Current Research International, 2025)
Flooding is the most common and damaging natural disaster in Illinois, largely due to climate change and human activities. This study explores the integration of Geographic Information Systems (GIS) in flood risk management across the state, focusing on the mapping of high-risk areas along major river corridors such as the Mississippi and Illinois Rivers. By utilizing survey data drawn from federal and state agencies participating in the Illinois Silver Jackets program, the research develops an interactive GIS-based flood map that visualizes vulnerable communities and supports dynamic spatial analysis. The GIS application/tool serves several functions: identifying flood-prone zones, enhancing emergency preparedness, informing land use and infrastructure planning, and improving public risk communication. The GIS tool uses real-time, user-friendly interface enables both technical and non-technical stakeholders to easily engage with flood data, fostering community resilience and informed decision-making. The findings highlight the value of collaborative, data-driven approaches in advancing proactive flood mitigation strategies throughout Illinois.